Sistemas de cultivo da cultura do fumo com ênfase às práticas de manejo e conservação do solo - Pellegrini, André (2006)
Soil management systems with minimum tillage and mulch are predominant in agriculture of Southern of Brazil. No-tillage for tobacco crop is not common and restricted to isolated places and only for some farmers that, through empiric tests and adaptation of equipments, search for soil preservation and increased yield. The objective of this work was study the main soil management systems for tobacco crop and possibilities of changing the traditional system of tobacco cropping, with emphasis on practices of soil management and conservation to maintain the levels of yield and decrease the environmental impacts. Six treatments, in a completely randomized blocks design with three replicates, were installed: PC conventional till; CMP - minimum tillage rest; CMA - minimum tillage oat; PDcC no-tillage with camalhão; PDcCC no-tillage with consolidated camalhão; PDsC no-tillage without camalhão. The experiment was installed in a watershed, located in Agudo-RS city, in the agricultural year of 2004, in a Leptosol. The maim physical parameters were soil moisture, measured with a time domain reflectometer (TDR), in the depths of 0-0,06, 0,06-0,12 and 0,12-0,18 m, and soil temperature in the depth of 0,05 m, measured with datalogger and termopars, both during 87 days in the growth cycle; total porosity, macroporosity, microporosity, bulk density and soil water retention curve (CRA), determined in the depths of 0-0,06, 0,06-0,12, 0,12-0,18 and 0,18-0,24 m, 30 days after transplantion (DAT) and on 135 DAT, except for CRA, in the depths of 0-0,06 and 0,06-0,12 m; water and soil loss by runoff, determined for eight rain events, in two blocks, with on area of 1.2 m2 of collection; potassium and phosphorus, soluble and total were determined for seven rain events; the root system, the distribution in the cultural profile, nutrients availability in the exploration area, dry mass for soil volume and maximum depth of roots were determined; mechanical resistance of soil was determined with a manual penetrometer to verify the depth of the root impediment; measures of the plants included the leaf area, determination of plant height, number of leaves and yield for hectare. The conservation managements reduced soil and water losses, providing smaller amplitude in the daily temperature variation, larges soil moisture, but the yield was smaller than PDsC. This result for the PDsC was directly influenced by the shallower roots depth, which was a consequence of several factors, such as: presence of impediment layer; absence of ridge; nutrients in the surface and favorable initial conditions of soil temperature and moisture. However, there was great interaction among factors, turning complex the explanation of the results obtained; therefore, factors such as nutrients in the surface favored the losses of P and K soluble, decreasing their availability to plants; the impediment layer reduced the volume of soil explored by the roots and the ability for water storage, whereas the management systems PDcCC and PDsC were outside the upper or lower limit of water availability, in the layer of 0 to 0,06 m, for about 15 days.